Assessment of Elderly's Nutritional status in Geriatric Homes at Al-Furat Al-Awusat Governorates - Mona Abdul Wahab Khaleel; Ali H. Mohammed (Kufa Journal for Nursing Sciences)
Objective: to assess the elderly's nutritional status through the dietary habits and anthropometric measures.